A pattern grammar approach to selected action verbs in LoCLaNT / Alfian Asmi - Alfian, Asmi (2017)
Pattern Grammar (Hunston & Francis, 2000) has been used in many studies as a source of insights into linguistic change. In Pattern Grammar, the behaviour of a lexical item is studied in which any change may reflect linguistic change. It has begun to attract the attention of many linguists to explore phraseology to analyse language use. However, most studies that use Pattern Grammar were based on native speaker‟s corpora. Little has been done on the Pattern Grammar which studies the learner language based on learner corpora (see Ellis et al., 2013, 2014; Romer et al. 2014). This study explores the development of learner language in the subset of LoCLaNT based on the Pattern Grammar approach. It focuses on the verb pattern (see Francis et al., 1996). The top five most frequent action verbs in the subset of LoCLaNT (i.e., GO, SAVE, SEE, SHOUT, FISH) are studied. This includes the variants of each verb (i.e., go, goes, going, went for GO). This study is in line with the observation of innovative and conventional language use as highlighted in Chau (2015). It can be observed from the analysis of this study that some verb patterns used by the learners are becoming more conventional. However, there are also instances of innovative pattern observed over time. This shows that the direction of the development of learner language is moving towards conventional yet still carries the innovation element.